Oltingugurtli vanna tuzlarini olish texnologiyasini takomillashtirish - Karimova Nodira Ikromjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the technological process for producing sulfur bath salts, which includes stages such as raw material selection, mixing, crystallization, drying, and packaging. The impact of technological parameters on the final product quality was studied, and optimal production conditions were determined based on experimental results. The research demonstrates that the physical-chemical properties of the obtained sulfur bath salts meet the requirements of current standards. The proposed technology ensures the production of a stable and high-quality product suitable for balneological and therapeutic applications.